2005
DOI: 10.1103/physrevd.72.024006
|View full text |Cite
|
Sign up to set email alerts
|

Cosmic censorship in higher dimensions. II.

Abstract: Generalizing earlier results on dust collapse in higher dimensions, we show here that cosmic censorship can be restored in gravitational collapse with tangential pressure present if we take the spacetime dimension to be N ≥ 6. This is under conditions to be motivated physically, such as the smoothness of initial data from which the collapse develops. The models considered here incorporating a non-zero tangential pressure include the Einstein cluster spacetime.

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
15
0

Year Published

2006
2006
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 7 publications
(15 citation statements)
references
References 26 publications
0
15
0
Order By: Relevance
“…25 it was shown that the condition that t ah is increasing, which is equivalent to the positivity of the first non-vanishing χ, is not only necessary but also sufficient for the local visibility of the central singularity (see also Refs. [32][33][34]. Furthermore it can be proven that if there is one outgoing radial null geodesic that escapes the singularity then there is necessarily a whole family of such geodesics.…”
Section: Trapped Surfaces and Outgoing Null Geodesicsmentioning
confidence: 99%
“…25 it was shown that the condition that t ah is increasing, which is equivalent to the positivity of the first non-vanishing χ, is not only necessary but also sufficient for the local visibility of the central singularity (see also Refs. [32][33][34]. Furthermore it can be proven that if there is one outgoing radial null geodesic that escapes the singularity then there is necessarily a whole family of such geodesics.…”
Section: Trapped Surfaces and Outgoing Null Geodesicsmentioning
confidence: 99%
“…In particular, the class of solutions that we find extend again vanishing radial stress models as dust [4,24]. We will find the complete spectrum of endstates, analyzing if and how it is modified by the dimension of the spacetime N. In particular, naked singularities will be proved to survive in any larger dimension, despite earlier results contained in [10,20] see discussion at the end.…”
Section: Introductionmentioning
confidence: 84%
“…There have been previous works trying to explain the endstate in terms of the kinematical properties of the spacetime, in particular the shear at initial time [10,20].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations